Heterogeneity and overlaps in nucleotide excision repair disorders. Issue 1 (22nd April 2019) - Ferri, Debora; Orioli, Donata; Botta, Elena
Abstract: Nucleotide excision repair (NER) is an essential DNA repair pathway devoted to the removal of bulky lesions such as photoproducts induced by the ultraviolet (UV) component of solar radiation. Deficiencies in NER typically result in a group of heterogeneous distinct disorders ranging from the mild UV sensitive syndrome to the cancer‐prone xeroderma pigmentosum and the neurodevelopmental/progeroid conditions trichothiodystrophy, Cockayne syndrome and cerebro‐oculo‐facio‐skeletal‐syndrome. A complicated genetic scenario underlines these disorders with the same gene linked to different clinical entities as well as different genes associated with the same disease. Overlap syndromes with combined hallmark features of different NER disorders can occur and sporadic presentations showing extra features of the hematological disorder Fanconi Anemia or neurological manifestations mimicking Hungtinton disease‐like syndromes have been described. Here, we discuss the multiple functions of the five major pleiotropic NER genes ( ERCC3/XPB, ERCC2/XPD, ERCC5/XPG, ERCC1 and ERCC4/XPF ) and their relevance in phenotypic complexity. We provide an update of mutational spectra and examine genotype‐phenotype relationships. Finally, the molecular defects that could explain the puzzling overlap syndromes are discussed. Abstract : Relationship between NER factors and human diseases